Designing professional development for change : a guide for improving classroom instruction - Bellanca, James (Thousand Oaks, Calif. : Corwin Press, 2009)
This substantially updated edition offers practical methods for designing professional development experiences that generate systemic change to improve teaching and learning.
Includes bibliographical references.
Keywords: Teachers -- In-service training -- Planning; Educational change